Examining the effect of halal perceived value and perceived risk on purchase intention: A mediating role of halal trust - Muchammad Agung Miftahuddin; Wiwiek Rabiatul Adawiyah; Refius Pradipta; Faizal Wihuda (Innovative Marketing, 2022)
Marketers in the rising halal Muslim consumerism must understand their clients’ behavior patterns to compete successfully. The purpose of this paper is to analyze the impact of halal perceived value, halal trust, and halal perceived risk on halal purchase intention among Muslim customers in Indonesia. Survey data analysis of 253 Muslim halal consumers was evaluated using structural equation modeling to scrutinize the empirical model fit. The results confirm that halal perceived value, perceived risk, and trust predict a significant amount of halal purchase intention. The study’s outcome also confirms that halal trust is a mediating variable through which halal perceived value and halal perceived risk affect halal purchase intention. This study contributes valuable insights into existing concepts of consumer halal trust influencing buying decisions and purchase intentions of halal products. This paper provides a practical foundation for managers to develop suitable halal marketing strategies that focus on creating value and reducing the risk perception to promote trust in consuming halal food products.